Role of the IgM Fc Receptor in Immunity and Tolerance - Liu, Jun; Wang, Ying; Xiong, Ermeng; Hong, Rongjian; Lu, Qing; Ohno, Hiroshi; Wang, Ji-Yang (Frontiers in Immunology, 2019)
Immunoglobulin (Ig) M is the first antibody isotype to appear during evolution, ontogeny and immune responses. IgM not only serves as the first line of host defense against infections but also plays an important role in immune regulation and immunological tolerance. For many years, IgM is thought to function by binding to antigen and activating complement system. With the discovery of the IgM Fc receptor (FcμR), it is now clear that IgM can also elicit its function through FcμR. In this review, we will describe the molecular characteristics of FcμR, its role in B cell development, maturation and activation, humoral immune responses, host defense, and immunological tolerance. We will also discuss the functional relationship between IgM-complement and IgM-FcμR pathways in regulating immunity and tolerance. Finally, we will discuss the potential involvement of FcμR in human diseases.